id like to thank you dan for your previous help.....it really helped me understand how the process worked

I have 2 questions if anyone could help me

with F(x) = square root of x - 3 and G(x) = 4x^2 + 3

a) write the function (G of F)(X) thats G of F of X

I came up with G(square root of x - 3) = 4(square root of x - 3)^2 + 3

G(x) = 4x + 12

b) find the domain...of the G of F of X ....

i have a few ideas but am kinda lost on this one

SECOND QUESTION

Given the one to one function G(x)= x^2+4 where X>

write g^-1(x)

write domain and range of G(x) G^-1(x)